Evaluation of the Career Guidance Program with the Context, Input, Process, and Product (CIPP) Model of the Career Center Field at the Indonesian Institute of Business and Technology INSTIKI - Ayu Gede Willdahlia; Aniek Suryanti Kusuma; Ni Kadek Nita Noviani Pande; Desak Made Dwi Utami Putra (Educare: Journal Educational and Multimedia, 2024)
This study aims to evaluate the educational program using the CIPP (Context, Input, Process, Product) model to assess the career services provided by the Career Center at INSTIKI and to evaluate the effectiveness of these services. The effectiveness of career counseling services is measured by how well the program's objectives have been achieved. The research uses a qualitative approach with a descriptive-analytic method, applying the CIPP evaluation model to assess each component: Context, Input, Process, and Product in the implementation of the career counseling program. The data sources for this study are the Career Center and alumni of INSTIKI. Data collection techniques involved interviews and observations with the Career Center, while additional data were gathered through questionnaires and documentation. The collected data were analyzed using triangulation techniques. The research findings indicate that the implementation of career planning and evaluation, career development, graduate placement, tracer studies, language services, and language development have a positive impact on the career advancement of graduates.